Innovative development in the agricultural sector of the Republic of Kazakhstan - Zhussupov, Y.A.; Baktymbet, S.S.; Shmarlovskaya, G.A. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the methods of innovative development of the agricultural complex of the Republic of Kazakhstan. It should be noted that the development of the economy has always been carried out on the basis of the introduction of innovations, «but the centuries-old slowdown of this process did not allow it to be tested». Modern innovative processes are distinguished by the fact that they become a condition for development, innovations «form the basis for the development of socio-economic systems, determine the pace and scale of their growth, structural changes». One of the innovations of the innovative organization of production in the agricultural sector of the economy of Kazakhstan is the formation of clusters. Currently, the peculiarity of domestic agriculture is the presence of a large number of scattered small farms less capable of perceiving innovations. Therefore, the innovation direction of entrepreneurship development in the agricultural sector may be the enlargement of enterprises through their combination or merger. Large enterprises are able to diversify their production in order to insure themselves against accidental risks. Thus, the innovation of the agricultural sector of the economy of Kazakhstan can be carried out in many areas, covering both improving methods of state support for agricultural producers and the creation of new structures such as a cluster. The main criterion for innovative development is the formation of competitive advantages.